2013
DOI: 10.1097/ta.0b013e3182826e84
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicenter comparison of levetiracetam versus phenytoin for early posttraumatic seizure prophylaxis

Abstract: Therapeutic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 16 publications
(17 reference statements)
2
77
0
4
Order By: Relevance
“…7,8,13,14,19,22 Even with this benefit, levetiracetam may not be used as commonly due to its higher cost relative to phenytoin. 13 Most patients received seizure prophylaxis within 24 hours of hospital admission and over half received the first dose of medication in the prehospital or ED setting, early in severe TBI care. This is important because studies have reported that first posttraumatic seizures are common within 24 hours of injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8,13,14,19,22 Even with this benefit, levetiracetam may not be used as commonly due to its higher cost relative to phenytoin. 13 Most patients received seizure prophylaxis within 24 hours of hospital admission and over half received the first dose of medication in the prehospital or ED setting, early in severe TBI care. This is important because studies have reported that first posttraumatic seizures are common within 24 hours of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Levetiracetam has only been researched as a potential option for seizure prophylaxis, 7,8,13,14,19 and initial studies have found it as effective as phenytoin but without similar side effects or the need to check drug levels in the blood. 7,8,13,14,19,22 Even with this benefit, levetiracetam may not be used as commonly due to its higher cost relative to phenytoin. 13 Most patients received seizure prophylaxis within 24 hours of hospital admission and over half received the first dose of medication in the prehospital or ED setting, early in severe TBI care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahajan et al reported a case of rapidly progressing distal limb ischemia resulting in compartment syndrome with arterial occlusion and thrombosis [31]. Finally, alternative drug regimens should be considered in situations in which efficacy has been shown to be non-inferior to phenytoin [2,10,60]. Any intravenous insertion sites should be monitored closely for pain, signs of extravasation, discoloration, or changes in perfusion and documented thoroughly [1,3].…”
Section: Preventionmentioning
confidence: 99%
“…Patients with severe TBI should receive phenytoin or levetiracetam for post-traumatic seizures [27][28][29] . Other risk factors for seizures are listed in Table 4.…”
Section: Adjunctive Therapiesmentioning
confidence: 99%